A Second Experimental Study the Application of a Teaching Plan for the Algorithms Subject in an Undergraduate Course in Computing using Active Methodologies - Garcia, Fabrício Wickey da Silva; Oliveira, Sandro Ronaldo Bezerra; Carvalho, Elielton da Costa (Informatics in education, 2023)
The contents taught in the programming subjects have a great relevance in the formation of computing students. However, these subjects are characterized by high failure rates, as they require logical reasoning and mathematical knowledge. Thus, establishing knowledge through the subject of algorithms can help students to overcome these difficulties and absorb the contents and skills required. Thus, this work aims to present and discuss the results of a second experiment on the application of a teaching plan composed of several active methodologies (Virtual Learning Environments, Coding Dojo, Gamification, Problem-Based Learning, Flipped Classroom and Serious Games) in an algorithms subject. Based on this experiment, it was evaluated whether there were learning gains compared to the learning acquired with the traditional method. Finally, an analysis was performed using the two-tailed Student-t approach, used for independent samples, which presented statistically significant results.